CRIMINAL LIABILITY OF A MOTHER FOR THE MURDER OF HER CHILD: A COMPARATIVE PERSPECTIVE BETWEEN THE OLD CRIMINAL CODE AND THE NEW CRIMINAL CODE (LAW No. 1 Of 2023) - Sari Sania Tampubolon; Suci Ramadani; Ismaidar (RADJA PUBLIKA, 2025)
This study aims to analyze the criminal liability of a biological mother who commits the murder of her child, as well as to compare the regulation and sentencing approaches between the former Criminal Code (KUHP) and the new KUHP under Law No. 1 of 2023. The research questions include: first, how criminal liability for a biological mother who kills her child is assessed from the elements of fault (mens rea) and capacity for responsibility (toerekeningsvatbaarheid) under Indonesian criminal law; and second, what are the differences in regulation and sentencing approaches for the crime of child murder by a biological mother in the former and new KUHP. The research method used is normative legal research with a comparative approach, through the study of statutory regulations, legal literature, and jurisprudence. The results show that the criminal liability of a biological mother who commits child murder is highly influenced by the analysis of the elements of fault and capacity for responsibility, including considerations of psychological disorders and social factors. The new KUHP under Law No. 1 of 2023 provides significant changes in the classification of offenses, sentencing limits, and a restorative justice approach that emphasizes the protection of children and victim recovery, compared to the former KUHP, which is more formalistic and retributive. Thus, this study emphasizes the need for a comprehensive understanding of the psychological aspects of the perpetrator and the harmonization of the application of criminal law in the context of child protection in Indonesia.